The limits of chemical homogeneity - the case of binary stars - Jamnik, Bor (Matrika, 2023)
The assumption of chemical homogeneity is a key assumption in many astrophysical studies, especially for Galactic archaeology and the methods of chemical tagging. It states that the chemical composition of the photospheres of two (or more) stars born from the same interstellar medium will remain the same for most of their lifetime. When chemically non-homogeneous binary stars are observed, this assumption is challenged. In this paper, some possible explanations for such binaries are discussed, and some example studies are presented.
Keywords: astrofizika; astrophysics; binary stars; chemical homogeneity; dvojne zvezde; galactic archaeology; galaktična arheologija; kemijska homogenost